Sosialisasi dan Edukasi Pemanfaatan Wedang Jahe pada Ibu Hamil di Deli Serdang Sumatera Utara - Hastuty, Yulina Dwi; Sitepu, Nadroh Br; Balqis, Yunashyfa Azzura; Afdillah, Gelis Putri; Shabil, Yunasya Pradita (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The purpose of this community service is to increase the knowledge of pregnant women and health workers at the Pratama Tanjung Clinic in Deli Serdang about alternative therapies or complementary therapies that are safe and can be used in overcoming nausea and vomiting in pregnant women, as well as overcoming the limitations of media used for educational activities in pregnant women. The solution to the problem offered is in the form of education with various media that have been prepared in advance related to the use of ginger tea in overcoming nausea and vomiting in pregnant women. The method was through counseling activities and demonstrations on using ginger tea as a complementary therapy in pregnant women and employees at the  Pratama Tanjung  Clinic, Deli Serdang. The media used are leaflets and pocketbooks that participants can read. The number of participants who participated in the activity was 42 people. The results obtained after community service activities showed an increase in knowledge from participants who were evaluated based on pre and post-test scores, activity participants also could access various sites containing health information.  It is hoped that with this community service activity, participants can apply the information obtained to overcome health problems faced both in the family environment and the surrounding community.